Interleukin-32: a Pandora’s box in human immunodeficiency virus infection - Abdalla, Abualgasim Elgaili; Manni, Emad; Elsaman, Tilal; Abosalif, Khalid; Alameen, Ayman Ali Mohammed; Mohamed, Malik Suliman; Ejaz, Hasan (Frontiers in Immunology, 2025)
Human immunodeficiency virus (HIV), which causes acquired immunodeficiency syndrome (AIDS), has been estimated to infect around 40.8 million people globally. This virus can persist and thrive in the presence of antiretroviral therapy, which is a major obstacle to HIV eradication. Therefore, understanding host immunological factors that underlie HIV persistence and pathogenesis can lead to the development of immunotherapeutic interventions. Interleukin-32 (IL-32) is an orphan cytokine with multiple isoforms and a complex signal transduction pathway that transmits through non-specific receptors. It is a multifunctional cytokine with dual immunomodulatory roles in HIV infection. IL-32 possesses both antiviral and pathogenic properties. It can block viral entry to target cells and reverse transcriptase activity. Also, IL-32 can promote the reactivation of latent reservoirs. Paradoxically, IL-32 can inhibit HIV-specific immune response and facilitate HIV latency in CD4+ T cells. IL-32 has a central pathological role in HIV-related cardiovascular disease. Here in this review, we will discuss the biology of IL-32 and the current state-of-the-art knowledge of how IL-32 orchestrates diverse immune responses during HIV infection. In addition, the potential therapeutic strategies that could modulate IL-32 activity or expression will be highlighted.